Critical Analysis of Current Trends in Public Health Management - Qashanin, Mujali Khursan Mohammed Al; Aljarah, Salem Saaed; jarah, Hamad Saeed Al; jarah, Amer Zafer Hussain Al; bahesh, Ahmad Saleh Hussain Al; AL-qareh, Ashraf Rizq yahya; Alahmari, Shroog khloofah; Alshaiban, Youssif Mohammed; Almahiya, Hussain Malfi; Ishaq, Razq Nasser Mohammed Al (Journal of Ecohumanism, 2024)
Today's public health management is undergoing significant transformations due to newly developing threats to global health. The direction of global development puts ever more emphasis on shifts like the integration of digital health technologies, the improvement of health equity, and the role of interdisciplinary collaboration within providing public health services. In this view, this review assesses the prevalent management trends in public health while weighing the impacts these trends have on health systems today. Technological advancement, policy change, and the requirement of resilience as future shocks and crises, including pandemics, chronic diseases, and social determinants of health, are key focuses of the analysis. The paper also draws attention to evidence-based practice and the emergence of interest in community-based health interventions for population well-being. It identifies future directions for further enhancing the competency of PHMD, including the priority areas of health system sustainability and transformation, development, and integration of approaches that expand access to health care and build health system resilience.